The attractiveness advantage at work: A cross-disciplinary integrative review - NAULT, Kelly A (Institutional Knowledge at Singapore Management University, 2020)
Compared with people of average attractiveness, the highly attractive earn roughly 20 percent more and are recommended for promotion more frequently. The dominant view of this “attractiveness advantage” is one of taste-based discrimination, whereby attractive individuals are preferred without justification in economic productivity. We conduct a comprehensive review of research on attractiveness discrimination, finding relatively more evidence that this phenomenon constitutes, to some extent, statistical (as opposed to solely taste-based) discrimination, in which decision makers assume that attractive people are more competent and discriminate based on instrumental motives. We then review research that speaks to whether decision makers might be correct in assuming that attractive workers are more productive, finding that the attractive possess a slight advantage in human and a notable advantage in social capital. We finally review studies evaluating whether an advantage exists beyond that explained by capital differences. We find that the current body of work provides inconclusive evidence of taste-based but relatively more conclusive evidence of statistical discrimination processes. Our integrative view suggests how attractiveness biases can be detected more effectively, and points to key directions for future research on the sources of the attractiveness advantage. We conclude by discussing the promise of an integrative approach to understanding other achievement gaps, such as those on the basis of gender, race, and social class.